Cytotoxic Phenanthrene, Dihydrophenanthrene, and Dihydrostilbene Derivatives and Other Aromatic Compounds from Combretum laxum - Eder Bisoli; Talita Vilalva Freire; Nídia Cristiane Yoshida; Walmir Silva Garcez; Lyara Meira Marinho Queiróz; Maria de Fátima Cepa Matos; Renata Trentin Perdomo; Fernanda Rodrigues Garcez (Molecules, 2020)
The chemical investigation of the roots and stems of Combretum laxum yielded a new dihydrostilbene derivative, 4′-hydroxy-3,3′,4-trimethoxy-5-(3,4,5-trimethoxyphenoxy)-bibenzyl (1), two phenanthrenes (2–3), and three dihydrophenanthrenes (4–6), along with one lignan, three triterpenoids, one aurone, one flavone, one naphthoquinone, and two benzoic acid derivatives. Their structures were determined by 1D and 2D nuclear magnetic resonance (NMR) spectroscopic techniques and/or mass spectrometry data. The occurrence of dihydrostilbenoid, phenanthrene and dihydrophenanthrene derivatives is unprecedented in a Combretum species native to the American continent. 2,7-Dihydroxy-4,6-dimethoxyphenanthrene, 2,6-dihydroxy-4,7-dimethoxy-9,10-dihydrophenanthrene and 5-O-methyl apigenin are novel findings in the Combretaceae, as is the isolation of compounds belonging to the chemical classes of aurones and naphthoquinones, while (+)-syringaresinol is reported for the first time in the genus Combretum. Compounds 1–6 were also evaluated for their in vitro cytotoxicity against five human cancer cell lines, and radical-scavenging ability against 1,1-diphenyl-2-picryl-hydrazyl (DPPH). 6-Methoxycoelonin (4) was the most cytotoxic against melanoma cells (IC50 2.59 ± 0.11 µM), with a high selectivity index compared with its toxicity against nontumor mammalian cells (SI 25.1). Callosin (6), despite exhibiting the strongest DPPH-scavenging activity (IC50 17.7 ± 0.3 µM), proved marginally inhibitory to the five cancer cell lines tested, indicating that, at least for these cells, antioxidant potential is unrelated to antiproliferative activity.